Effect of short-term oral nutrients after hospital discharge on postoperative muscle loss and survival in gastric cancer patients - Lu, Yangbin; Yang, Jiaqi; Jiang, Zhixuan; Huang, Jianqiang; Shen, Xian; Lu, Yuwen (Frontiers in Oncology, 2026)
AimA decrease in skeletal muscle mass in patients with gastric cancer following surgery is closely related to tumor recurrence and poor prognosis. Postoperative enteral nutrition support can accelerate the postoperative recovery of patients with gastric cancer. We aimed to analyze the effectiveness of short-term oral nutritional supplements(ONS) in attenuating postoperative skeletal muscle mass loss in gastric cancer patients after hospital discharge and the impact on long-term prognosis.MethodsThis study included patients who underwent radical gastrectomy at our center between 2014 and 2019. Univariate and multivariate logistic regression analyses were used to analyze the effectiveness of short-term oral nutrition for reducing postoperative skeletal muscle mass loss in patients with gastric cancer. Using cox regression to analyze the effect of ONS and each covariate on overall survival (OS).ResultsONS attenuated postoperative skeletal muscle loss, and it can improve the prognosis of patients, especially the elderly, those with poor nutritional status, anemia, and patients who have undergone total gastrectomy.ConclusionsShort-term oral nutrition is an independent protective factor for preventing skeletal muscle mass loss in patients with gastric cancer after surgery. Oral nutrition after surgery can reduce short-term muscle mass loss and is helpful in lowering the risk of death for patients.